2013
DOI: 10.1016/j.radmeas.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark measurements and simulations of dose perturbations due to metallic spheres in proton beams

Abstract: Monte Carlo simulations are increasingly used for dose calculations in proton therapy due to its inherent accuracy. However, dosimetric deviations have been found using Monte Carlo code when high density materials are present in the proton beam line. The purpose of this work was to quantify the magnitude of dose perturbation caused by metal objects. We did this by comparing measurements and Monte Carlo predictions of dose perturbations caused by the presence of small metal spheres in several clinical proton th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…This is because multiple coulomb scattering of protons occurs in a greater amount than carbons. 11 , 12 , 14 On the other hand, contribution of fiducial markers to dose distributions of carbon ions is small, which is similar to the results of another study. 16 In the present study, the DVH of a target was simulated to evaluate the effect of markers on dose coverage to a target.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is because multiple coulomb scattering of protons occurs in a greater amount than carbons. 11 , 12 , 14 On the other hand, contribution of fiducial markers to dose distributions of carbon ions is small, which is similar to the results of another study. 16 In the present study, the DVH of a target was simulated to evaluate the effect of markers on dose coverage to a target.…”
Section: Discussionsupporting
confidence: 89%
“…The dose perturbation in the case of carbon ions evaluated in our study is much smaller than those that were reported in the case of protons. This is because multiple coulomb scattering of protons occurs in a greater amount than carbons 11,12,14 . On the other hand, contribution of fiducial markers to dose distributions of carbon ions is small, which is similar to the results of another study 16 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Equivalent dose from secondary neutrons was calculated in each voxel using the Monte Carlo Proton Radiotherapy Treatment Planning (MCPRTP) system [ 9 , 23 , 26 , 27 ]. The MCPRTP system was modified prior to this study to include a lattice tally instead of a mesh tally to calculate dose within the patient [ 28 ], an upgrade of the dose engine to version 2.7c of the Monte Carlo N-Particle eXtended code [ 29 ], more-specific isotopic materials cards that call cross-section tables when available, the most up-to-date data libraries, an improved multiple Coulomb scattering algorithm [ 30 , 31 ], a reduced bin size for more precise proton stopping power, and removal of triton and 3 He tracking. The system was validated by comparing its results to the results of previous studies and measured data.…”
Section: Methodsmentioning
confidence: 99%
“…Others have examined the effects of MCS in larger metal objects on clinical proton beams and characterized the suitability of approximate methods to predict MCS in practical clinical applications (Herault et al , 2005; Stankovskiy et al , 2009; Newhauser et al , 2013). …”
Section: Proton Interaction Mechanismsmentioning
confidence: 99%